Concyclic CH-π arrays for single-axis rotations of a bowl in a tube - Taisuke Matsuno (Nature Portfolio, 2018)
The weak and directional CH-π hydrogen bond has rarely been exploited in the design of supramolecular complexes and molecular machinery. Here, the authors construct a bowl-in-tube complex stabilized solely by concyclic CH-π hydrogen bonds, and show that the guest exhibits single-axis rotational motion despite tight association with the host.